2009
DOI: 10.1007/s00405-009-1167-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of the tumor necrosis factor-alpha −308 G/A polymorphism with nasal polyposis

Abstract: Nasal polyposis (NP) is a chronic inflammatory disease in which several molecular and cellular interactions play important roles. Tumor necrosis factor-alpha (TNF-alpha) is a major pro-inflammatory cytokine with a key role in immune inflammatory responses in NP. Altered levels of TNF-alpha, which may occur due to polymorphisms in the TNF-alpha promoter region, may also be associated with NP susceptibility. Given these facts, we investigated the possible association of the TNF-alpha -308 G/A single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Polymorphisms of TNF-α promoter are associated with high levels of TNF-α and have been studied as a determinant of susceptibility to numerous diseases [12,[21][22][23][24][25]. A study that examined inflammatory cytokines and Fcγ receptor polymorphisms in chronic childhood ITP reported that polymorphisms in 2 low-affinity FcγR genes (IIIA and IIIB) and 2 proinflammatory cytokine genes (TNF and LTA) were associated with chronic childhood ITP [7].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of TNF-α promoter are associated with high levels of TNF-α and have been studied as a determinant of susceptibility to numerous diseases [12,[21][22][23][24][25]. A study that examined inflammatory cytokines and Fcγ receptor polymorphisms in chronic childhood ITP reported that polymorphisms in 2 low-affinity FcγR genes (IIIA and IIIB) and 2 proinflammatory cytokine genes (TNF and LTA) were associated with chronic childhood ITP [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the North America region, Randolph et al (21) found that TNF-α gene promoter region allele frequency did not affect asthma formation, whereas Witte et al (22) found the A allele to be a risk factor. The different results in the Turkish population (7,8, and our study) can be explained by genetic variations in different regions of the country, patient selection criteria, and differences in study design. Moreover, the effect of allelic frequencies and genotypes of the TNF-α gene promoter region on the transcription of TNF-α is not clear.…”
Section: Discussionmentioning
confidence: 54%
“…Single nucleotide polymorphisms (SNPs) in these pro-inflammatory mediators have been studied for genetic susceptibility to NP development, but the literature findings regarding the dominant genotype or allele causing NP formation are conflicting. Some authors claim that the TNF-α GA polymorphism in the -308 promoter region is a risk factor for NP development, whereas others have found that the A allele frequency is a risk factor (7)(8)(9). Some authors have found no relationship between the TNF-α GA polymorphism and NP development (4,10).…”
Section: Introductionmentioning
confidence: 99%
“…Batikhan et al showed that TNF-a-308G > A single nucleotide polymorphism (SNP) may play a role in the etiology of nasal polyposis (10).…”
Section: Discussionmentioning
confidence: 99%